Echocardiographic Image Quality Deteriorates with Age in Children and Young Adults with Duchenne Muscular Dystrophy - Power, Alyssa; Poonja, Sabrina; Disler, Dal; Myers, Kimberley; Patton, David J.; Mah, Jean K.; Fine, Nowell M.; Greenway, Steven C. (Frontiers in Cardiovascular Medicine, 2017)
Background: Advances in medical care for patients with Duchenne muscular dystrophy (DMD) have resulted in improved survival and an increased prevalence of cardiomyopathy. Serial echocardiographic surveillance is recommended to detect early cardiac dysfunction and initiate medical therapy. Clinical anecdote suggests that echocardiographic quality diminishes over time, impeding accurate assessment of left ventricular systolic function. Furthermore, evidence-based guidelines for the use of cardiac imaging in DMD, including cardiac magnetic resonance imaging, are limited. The objective of our single-centre, retrospective study was to quantify the deterioration in echocardiographic image quality with increasing patient age and identify an age at which cardiac magnetic resonance imaging should be considered. Methods: We retrospectively reviewed and graded the image quality of serial echocardiograms obtained in young patients with DMD. The quality of 16 left ventricular segments in two echocardiographic views was visually graded using a binary scoring system. An endocardial border delineation percentage score was calculated by dividing the number of segments with adequate endocardial delineation in each imaging window by the total number of segments present in that window and multiplying by 100. Linear regression analysis was performed to model the relationship between the endocardial border delineation percentage scores and patient age. Results: Fifty-five echocardiograms from 13 patients (mean age 11.6 years, range 3.6-19.9) were systematically reviewed. By 13 years of age, 50% of the echocardiograms were classified as suboptimal with ≥30% of segments inadequately visualized, and by 15 years of age 78% of studies were suboptimal. Linear regression analysis revealed a negative correlation between patient age and endocardial border delineation percentage score (r = -2.49, 95% confidence intervals -4.73, -0.25; p=0.032), with the score decreasing by 2.5% for each 1 year increase in age. Conclusions: Echocardiographic image quality declines with increasing age in DMD. Alternate imaging modalities may play a role in cases of poor echocardiographic image quality.